2019
DOI: 10.13166/jms/112280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Teachers’ Opinions on Learning Difficulties of Stuttering Primary Students In Terms of Terms of First Literacy

Abstract: ObjectivesIn this study, researchers aimed to (1) investigate how stuttering affects the learning process of first reading and writing, and (2) reveal the problems encountered by children with stuttering during the first literacy process and (3) shed light on further research in this area. Material and methodsThe research is a descriptive study to determine the problems that students with stuttering have experienced in the process of learning first literacy skills. In this study, semi-structured interviewing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As a result, the maximum possible score in TATS-Persian, like the original version, is 144 and the minimum possible score is zero. Higher scores indicate a more favorable attitude of the teacher towards stuttering [1].…”
Section: Teacher's Attitude Towards Stuttering Inventorymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the maximum possible score in TATS-Persian, like the original version, is 144 and the minimum possible score is zero. Higher scores indicate a more favorable attitude of the teacher towards stuttering [1].…”
Section: Teacher's Attitude Towards Stuttering Inventorymentioning
confidence: 99%
“…tuttering is one of the common speech disorders, which is characterized by the main features such as block, prolongation, and repetition of words or syllables and secondary features such as extra body movements or tightness within the face, hands, body, difficulty in rhythm, and mastery of speaking [1]. Research has shown that children with the stuttering disorder are greatly influenced by those around them, and this can affect their communication skills and progress in treatment [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 Stammering is characterized by incoherent repetitions, pauses, inappropriate vowel production, unintended breaks, spasms, and emotional swings while speaking resulting in serious complications in communication. 2 There is no specific age for stammering. 3 It involves various genetic and environmental factors responsible for the occurrence of this specific disability.…”
Section: Introductionmentioning
confidence: 99%